TrendsofAntibiotic Resistance in ESKAPEPathogensinMbarara Regional Referral Hospital (2015–2022), South Western, Uganda - Joel Bazira; Pauline Petra Nalumaga; Balukhu Quraishi; Abel W. Walekhwa; Mugisha Lawrence; Jacob Stanley Iramiot (Canadian Journal of Infectious Diseases and Medical Microbiology, 2025)
Introduction: Antimicrobial resistance remains a global threat, with increasing infection and death rates. The World Health Organization identified Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. (ESKAPE) as priority pathogens due to their increased antibiotic resistance development. Tis study assessed the resistance patterns of ESKAPE pathogens from 2015 to 2022 in Mbarara Regional Referral Hospital, Uganda. Methods: A retrospective study was conducted by reviewing retrieved data from WHONET. Tis is the laboratory software used in the microbiology laboratory in the Department of Microbiology, Mbarara University of Science and Technology (MUST), which receives samples from both the outpatient and the inpatient departments of Mbarara Regional Referral Hospital. Results: A total of 5733 bacterial isolates were recovered, of which, 4822 were ESKAPE pathogens from the collected clinical specimens including blood, stool, urine, swabs, cerebral spinal fluid, wounds, and sputum. Staphylococcus aureus (4291, 74.8%) was the most frequently isolated pathogen followed by Klebsiella pneumoniae (345, 6.0%). The bacteria categorized as ESKAPE pathogens showed significant rates of multidrug resistance. Ampicillin showed the highest resistance followed by ciprofoxacin. Conclusion: The significant prevalence of antimicrobial resistance to penicillin, ciprofoxacin, and tetracycline in ESKAPE bacteria emphasizes the significance of enhancing antimicrobial surveillance and infection-prevention and management initiatives within the country.
Keywords: Antimicrobial resistance; ESKAPE pathogens; Southwestern Uganda